2019
DOI: 10.7567/1882-0786/ab56e2
|View full text |Cite
|
Sign up to set email alerts
|

Deeply-scaled GaN-on-Si high electron mobility transistors with record cut-off frequency f T of 310 GHz

Abstract: A deeply-scaled GaN-on-Si high electron mobility transistor with a record-high cut-off frequency (fT) of 310 GHz has been demonstrated. The device has an InAlN/GaN heterojunction structure, a source–drain spacing of 400 nm, and a gate length of 40 nm. The device exhibited a high drain current of 2.34 A mm−1, a peak transconductance of 523 mS mm−1, and a gate-to-drain breakdown voltage (BVgd) of 15 V. A Johnson’s figure-of-merit (FOM = fT × BV) of 4.65 THz V has been achieved, which is comparable to those repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Benchmark of cut-off frequency versus L G [143][144][145][146][147][148] illustrates the importance of gate length shrinking to increase f T . Both NTU [149] and Intel [143] demonstrated 40 nm gate length GaN HEMT on Si with f T /fmax higher than 300 GHz, though the current record f T /fmax values of 450 GHz was achieved by HRL [144] with the 20 nm Gate GaN on SiC technology. GaN HEMT on Si also have high load pull result comparable to SiC substrate [155], nevertheless, GaN HEMT on Si substrate shows high potential.…”
Section: Rf Gan Performance Si Substratementioning
confidence: 99%
“…Benchmark of cut-off frequency versus L G [143][144][145][146][147][148] illustrates the importance of gate length shrinking to increase f T . Both NTU [149] and Intel [143] demonstrated 40 nm gate length GaN HEMT on Si with f T /fmax higher than 300 GHz, though the current record f T /fmax values of 450 GHz was achieved by HRL [144] with the 20 nm Gate GaN on SiC technology. GaN HEMT on Si also have high load pull result comparable to SiC substrate [155], nevertheless, GaN HEMT on Si substrate shows high potential.…”
Section: Rf Gan Performance Si Substratementioning
confidence: 99%
“…Xie et al reported f T / f max of 310/40 GHz with L G = 40 nm, but with an R C of 0.16–0.18 Ω mm using alloyed Ohmic contacts. [ 10 ] While the trends in f T reported in these devices are observed to increase, the effective electron velocity is still far from the theoretical limits. A high effective electron velocity and a low parasitic delay result in a good f T –L G product in a device.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, GaN‐on‐SiC wafer size being limited to 6 inch is a bottleneck in scalability and hence, GaN‐on‐Si HEMTs are being increasingly explored for radio frequency (RF) and power performance. [ 5–13 ]…”
Section: Introductionmentioning
confidence: 99%
“…The device presents a maximum drain current (Id, max) of 2.8 A/mm, a peak extrinsic transconductance (gm) of 0.66 S/mm, and a current/power gain cutoff frequency (fT/fmax) of 250/204 GHz. H. Xie et al reported that a record fT of 310 GHz was achieved on a InAlN/GaN HEMT on Si with a 40-nm gate length [6]. P. Cui et al demonstrated an 80-nm-gate-length InAlN/GaN HEMT on Si with a record high on/off current (Ion/Ioff) ratio of 1.58 × 10 6 , a steep subthreshold swing (SS) of 65 mV/dec, and a fT of 200 GHz, resulting in a record high fT × Lg = 16 GHz•µm [7].…”
Section: Introductionmentioning
confidence: 99%